Blood eosinophil count and exacerbation risk in patients with COPD. - Kerkhof, M; Sonnappa, S; Postma, D; Brusselle, G; Agustí, A; Anzueto, A; Jones, R; Papi, A; Pavord, I; Pizzichini, E; Popov, T; Roche, N; et al. (European Respiratory Society, 2017)
Blood eosinophil counts are a promising biomarker to guide therapy for chronic obstructive pulmonary disease (COPD). We examined the association between blood eosinophil counts in stable COPD and exacerbations in the following year in real-life patients, and assessed whether the relationship differs in specific patient subgroups. We conducted a historical follow-up study using anonymized medical records for patients ≥40 years with spirometrically confirmed COPD and a smoking history. We estimated the association between eosinophil counts and the number of exacerbations during 1 follow-up year, adjusted for confounders assessed in the preceding year. Of 8,318 patients with COPD (56% male; mean [SD] age 70 [10] years), 87.7% had eosinophil counts ranging from 0.05 to <0.45x109/L (reference), 8.9% had elevated counts (≥0.45x10911 /L), and 3.4% low counts (<0.05x10912 /L). Patients with elevated counts had an overall 13% higher rate of exacerbations during follow-up than the reference group (RR 1.13; 95% CI 1.01–1.26). This increased exacerbation rate was restricted to ex-smokers (RR 1.32; 1.15–1.51) and not found in current smokers (RR 0.86; 0.71–1.05). Low counts were not associated with exacerbation rates. Elevated blood eosinophil counts may potentially serve as a biomarker of COPD exacerbation risk, yet only in some subgroups of COPD.